The manager’s role in successful lean implementation: evidences from Vietnamese enterprises : Luận văn ThS. Kinh doanh: 603401 - Le, The Nguyen Trung Hieu (2019)
Lean Production is a philosophical view and practices centered on improving customer value by eliminating activities which have no values from production operations. Recently, Lean Production is experiencing an increasing interest, mainly as its principles and practices is especially suitable for the situation of scare resources and unstable economy. Despite this, scholar work of Lean Production, particularly exploration on the management of Lean implementation, stays limited. In this research, the author conducted 16 interviews and a survey of 50 respondents to explore the behaviors performed by effective Lean leaders and managers. The result was the use of more positive relations-oriented behaviors such as: active listening and sharing, empowering and showing care to employees, training and coaching, showing positive attitudes, be open in information sharing while the uses of task monitoring such as monitoring, clarifying are seen to be less popular, except for the increase practice of visualization. Behaviors towards changes such as envisioning change and encouraging new ideas and innovations are promoted. The study compares the findings with modern leadership theories, as well as proposes implications for Lean practitioners. The end includes limitations and suggestions for future research.